Insecticide susceptibility of bemisia tabaci to karate® and cydim super® and its associated carboxylesterase activity - S.W. Avicor; V.Y. Eziah; E.O. Owusu; M.F.F. Wajidi (Universiti Kebangsaan Malaysia, 2014)
Bemisia tabaci is a pest of several economic crops worldwide and is mostly managed in Ghana by farmers through the use of insecticides. However, vegetable farmers have recently expressed concerns about the susceptibility of B. tabaci to insecticides. Hence, the susceptibility status of field populations of B. tabaci on cassava, okra and tomato in vegetable growing sites in Accra to two commonly used insecticides, Karate® 2.5 EC (λ-cyhalothrin) and Cydim Super® (36 g Cypermethrin + 400 g Dimethoate per litre), using a modified dipping method and their carboxylesterase activity levels were assessed. The LC50 values of the B. tabaci populations to the insecticides were low and ranged from 0.12-0.55 mL/L to 0.07-0.36 mL/L for Karate® and Cydim Super®, respectively. There was a wide variation in carboxylesterase activity levels of the insect populations with high levels recorded in some of the populations. The elevated activity levels could negatively impact on future whitefly management methods. This study provides baseline information on the insecticide resistance status and carboxylesterase levels of whitefly populations in these areas and for monitoring future insecticide resistance development.